KEGIATAN LITERASI MELALUI MENDONGENG SEBAGAI UPAYA PENANAMAN MINAT BACA SISWA KELAS III SD NEGERI 4 KUTOSARI TAHUN AJARAN 2019/2020 - Nurul Safitri; Rokhmaniyah Rokhmaniyah; Moh Salimi (Universitas Sebelas Maret, 2021)
Indonesians have low reading interest.The study aimed to describe the implementation of literacy activity through storytelling and the impact on third grade students’ reading interest of SD N 4 Kutosari. It was case study. The subjects were students and teacher of third grade of SD N 4 Kutosari. The data collection techniques were observation, interviews, questionnaire, and document study. The result showed that were three stage of implementation of literacy activities through storytelling: (a) preparation, (b) storytelling activity, (c) evaluation. The implementation of literacy activities through storytelling have good impact on students’ reading interest